2016
DOI: 10.1111/apa.13546
|View full text |Cite
|
Sign up to set email alerts
|

Extended‐spectrum β‐lactamase‐producing bacteria caused less than 5% of urinary tract infections in a paediatric emergency centre

Abstract: The prevalence of febrile ESBL urinary tract infections was less than 5% in a paediatric emergency department. This low rate was not high enough to justify changing our guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…A high rate of antibiotic resistance for E. coli strains, in particular, has been identified in Europe and North America ( 8 , 16 , 17 ). Urinary E. coli expressing ESBLs in Asia has already reached about 60% ( 18 , 19 ), but remains fortunately low in Europe ( 13 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of antibiotic resistance for E. coli strains, in particular, has been identified in Europe and North America ( 8 , 16 , 17 ). Urinary E. coli expressing ESBLs in Asia has already reached about 60% ( 18 , 19 ), but remains fortunately low in Europe ( 13 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the p values in Table 1, the odds ratios of male gender and chronic diseases as risk factors for ESBL UTIs are not statistically significant, which can be seen from the 95% confidence interval limits of the odds ratios as they include one . Furthermore, Jacmel et al.…”
mentioning
confidence: 72%
“…In this issue of Acta Paediatrica , Jacmel et al. report on the occurrence of ESBL among children with urinary tract infections (UTIs) in one French paediatric emergency centre. They found that <5% of UTIs were caused by ESBL‐producing bacteria.…”
mentioning
confidence: 99%
“…The classification of antibiotics was very heterogeneous among selected studies ( Tables S1 and S2 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Overall antibiotic exposure (i.e., without specifying a drug or class) was analyzed as a risk factor in 77% (36/47) of studies, while cephalosporins, (fluoro)quinolones, and penicillins were frequently individualized, with various sub-classifica...…”
Section: Studies’ Epidemiological Key Points: Challenges Findings And...mentioning
confidence: 99%